A CLINICAL STUDY OF EFFECT OF PATALA KSHAR IN THE MANAGEMENT OF MUTRAVAGHATA WITH SPECIAL REFERENCE TO BENIGN PROSTATE HYPERPLASIA - Ranjwe, *Nandkishor; Badwe, Yogesh; Vaidya, Umesh (International Journal of Ayurveda and Pharma Research, 2016)
Vatashtila described by Acharya Sushruta is very much similar to Benign prostate hyperplasia. No doubt that it is disease which is difficult to cure and many times requires surgical intervention. All the other treatment modalities in modern science are very costly to cure the BPH. Hence we have to face many problems to treat BPH. Reviewing all the things â€œA clinical study of Patalakshar in the management of Mutraghat with special reference to Benign Prostate Hyperplasiaâ€ was selected for dissertation. In this study Patala kshar given orally to the BPH patients and follow up taken on 0th, 7th and 15th day. Tamsulosin was given to control group and follow up taken on same days as trial groups. Then we were found that Patala kshar effect is most of similar to modern conservative treatment tamsulosin. On the basis of statistical analysis it concluded that Patala kshar is similarly effective to tamsulosin.